Exploring critical factors of tourist satisfaction: a study on Islamic tourists destinations in Malaysia - Haque, A. K. M. Ahasanul; Khan, Abdul Highe (National Academy of Management, 2013)
Tourism industry is one of the largest service industries in Malaysia and it has great impact on national economy. The main objective of this study is to explore the factors that lead to tourist's satisfaction in terms of Islamic tourist destinations. This research will conduct 3 stages of data analysis: exploratory factor analysis; confirmatory factor analysis and structural equation model ing to test the hypothesis. This research is necessary to provide a better understanding of Muslim tourist satisfaction in Malaysian Islamic tourist destination in different facets. The identification of significant factors influencing Muslim tourist satisfaction to revisit Malaysia for the purpose of making strategic marketing plans can be made to encourage Muslim tourists to visit Mala